FIGURATIVE LANGUAGE APPLIED IN MELANIE MARTINEZ’S K-12 ALBUM - Darmawan, Anisa Safira; Widyaningrum, Agnes (Universitas 17 Agustus 1945 Semarang, 2024)
This research paper is focused to find figurative language in the lyrics of the song